Continuities and discontinuities in the cultural evolution of global consciousness - Zhang, Robert Jiqi; Liu, James H.; Lee, Michelle; Lin, Mei Hua *; Xie, Tian; Chen, Sylvia Xiaohua; Leung, Angela K.-y; Lee, I-Ching; Hodgetts, Darrin; Valdes, Evan A.; Choi, Sarah Y. (The Royal Society, 2024)
Global consciousness (GC), encompassing cosmopolitan orientation, global orientations (i.e. openness to multicultural experiences) and identification with all humanity, is a relatively stable individual difference that is strongly associated with pro-environmental attitudes and behaviours, less ingroup favouritism and prejudice, and greater pandemic prevention safety behaviours. Little is known about how it is socialized in everyday life. Using stratified samples from six societies, socializing institution factors correlating positively with GC were education, white collar work (and its higher income) and religiosity. However, GC also decreased with increasing age, contradicting a ‘wisdom of elders’ transmission of social learning, and not replicating typical findings that general prosociality increases with age. Longitudinal findings were that empathy-building, network-enhancing elements like getting married or welcoming a new infant, increased GC the most across a three-month interval. Instrumental gains like receiving a promotion (or getting a better job) also showed positive effects. Less intuitively, death of a close-other enhanced rather than reduced GC. Perhaps this was achieved through the ritualized management of meaning where a sense of the smallness of self is associated with growth of empathy for the human condition, as a more discontinuous or opportunistic form of culture-based learning.